2018
DOI: 10.1002/aic.16372
|View full text |Cite
|
Sign up to set email alerts
|

Quantum chemistry calculation aided design of chiral ionic liquid‐based extraction system for amlodipine separation

Abstract: Amlodipine is a widely used medication in treating hypertension, which is also known as a chiral compound. So far efforts have been made to obtain optically pure (S)‐amlodipine because (R)‐amlodipine has poor efficacy and is related to undesirable side effects. However, the available separation methods for amlodipine are still unsatisfactory. Recently, chiral separation has become a promising application of chiral ionic liquids (CILs), because the structural designability enables them adjustable separation eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…First, it is shown in Figure 9a that regardless of the imidazolium cations, the S HB (t) curves of anions with ibuprofen always decrease in the order: 6 ] − , suggesting that the HB interac- withdrawing fluorinated groups, which can be clearly supported by the results of Figures 3 and 4a. Furthermore, the previous experiments 20,33 and MD calculations 34,[36][37][38] also proved that the strong HB interactions between ILs and solutes played an essential role in the extractive separation and dissolution of drugs. Therefore, as an excellent IL for the solvation of ibuprofen, its anion, as a HB acceptor, should have a strong HB acceptability in order to interact strongly with the hydroxyl proton of ibuprofen.…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…First, it is shown in Figure 9a that regardless of the imidazolium cations, the S HB (t) curves of anions with ibuprofen always decrease in the order: 6 ] − , suggesting that the HB interac- withdrawing fluorinated groups, which can be clearly supported by the results of Figures 3 and 4a. Furthermore, the previous experiments 20,33 and MD calculations 34,[36][37][38] also proved that the strong HB interactions between ILs and solutes played an essential role in the extractive separation and dissolution of drugs. Therefore, as an excellent IL for the solvation of ibuprofen, its anion, as a HB acceptor, should have a strong HB acceptability in order to interact strongly with the hydroxyl proton of ibuprofen.…”
Section: Resultsmentioning
confidence: 75%
“…Previous experimental 23,24,29,35 and theoretical studies [37][38][39][40] have reported that the HB formed between ILs and drugs is probably one of the main factors for improving drug solvation in ILs. The carboxyl group of ibuprofen owns a HB acceptor (C O) site and HB donor (O H) site.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, functional ILs with chiral centers, called chiral ionic liquids (CILs), attract considerable attentions and are applied in a vast range of areas, for instance asymmetric synthesis , chromatography , spectroscopy , LLE , and dynamic separation . Recently, Ding et al developed a high‐efficient CIL‐based LLE system for racemic amlodipine separation with the assistance of quantum chemistry. Greño et al investigated the effect of the combined use of γ‐cyclodextrin and a CIL on the enantiomeric separation of homocysteine in CE.…”
Section: Introductionmentioning
confidence: 99%